The influence of influencers and Instagram social media on purchasing decisions with consumer trust as an intervening variable for nature lovers in DKI Jakarta - Muhammad Arjuna Satriawan; Bono Prambudi; Lela Nurlaela Wati (Priviet Social Sciences Journal, 2025)
This study aims to analyze and understand the factors influencing purchasing decisions for Eiger products among nature lovers in DKI Jakarta, with a particular focus on the roles of influencer marketing, Instagram-based social media engagement, and consumer trust as mediating variables. The originality of this study lies in its integration of consumer trust as an intervening mechanism within the influencer marketing context, specifically targeting a niche market of outdoor enthusiasts. A descriptive quantitative approach was employed using structural equation Modeling with the partial least squares (SEM-PLS) method. Data were collected from 220 respondents through an online questionnaire and analyzed using SmartPLS version 4.0.0. The results indicate that influencer marketing significantly influences consumer trust, whereas Instagram social media engagement does not have a direct effect on purchasing decisions. Further, consumer trust mediates the relationship between influencer marketing and purchasing decisions, reinforcing the strategic value of building trust in influencer-driven campaigns. This study is limited to Instagram users in DKI Jakarta and focuses solely on the Eiger brand, which may constrain the generalizability of the findings. Nevertheless, this study offers new insights into consumer behavior in the outdoor product segment and contributes to the literature on digital marketing and trust-based purchasing dynamics across generational cohorts.